Functional analysis of a lignin biosynthetic gene in transgenic tobacco - Mbewana, Sandiswa (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScAgric (Viticulture and Oenology. Wine Biotechnology))--University of Stellenbosch, 2010.